Edukasi Penggolongan Obat Dan “Dagusibu” Kepada Ibu-Ibu Majelis Taklim Di Rumah Yatim Al-Amin-Tangerang Selatan - Chusun Chusun; Mira Husni Sanjaya; Nabila Nuha (Jurnal Abdi Masyarakat Kita, 2022)
Self-medication is often carried out by the community. Education on Drug Classification and "DAGUSIBU", is one of the efforts that can be done in increasing public knowledge, when people are doing their own treatment. This education was attended by 40 participants from the Taklim Mujahidin Council and Madrasah Aliyah students from the Al Amin Orphanage Foundation-South Tangerang. This education is carried out through interactive delivery of material accompanied by a demonstration of the packaging of over-the-counter drugs, limited free medicines prescription drugs including narcotics, followed by a question and answer session or discussion. From the results of the Pre and Post test, it can be seen that there is an increase in knowledge of about 20%, from 50.5% to 69.8% (∞ 70%). At the end of the event, an evaluation of activities was also carried out using a questionnaire that had been tested for validity and reliability.